PANDANGAN MAHASISWA CALON GURU BIOLOGI DAN GURU IPA PESERTA PELATIHAN PENGEMBANGAN PROFESI TENTANG HAKIKAT SAINS - Yusuf Hilmi Adisendjaja; Nuryani Rustaman; Djam'an Satori; Sri Redjeki (Universitas Sultan Ageng Tirtayasa, 2016)
This study assessed biology students’ and science teachers’ views on the nature of science (NOS). Aspects of NOS included science definition, empiric, experiment, experiment in scientific knowledge development, tentative, scientific theories and laws, subjective (theory-laden), social and culture embededness, creative and imaginative. Participants were 34 undergraduate preservice biology teachers at seventh semester and 23 science teachers enrolled in the training. An open-ended questionaire of NOS (VNOS-C) adapt from Lederman, et al., (2002) coupled with some individuals interviews was used to assess participants’ NOS views before and after training. All answers were categorized based on Abd-El-Khalick & Akerson (2009): informed, partially informed, and naive Before training, the majority of participants held naive views of the target NOS except subjective. During the training explisit reflective approaches were used with inquiry teaching. Post-training assessment indicated that there were improvement of participants’ views on NOS. Nearly all aspects were improve with varied percentage of improvement, the range were 10%-55%, except social and culture embededness decreased. The result of the present study suggested the teaching method in preservice and inservice teacher education should more intensively use inquiry teaching and emphasize on nature of science.